A Preclinical Study Comparing the Activity and Potency of OnabotulinumtoxinA and PrabotulinumtoxinA - Rupp DC; Canty D; Rhéaume C; Sondergaard B; Niño C; Broide RS; Brideau-Andersen AD (Dove Medical Press, 2023)
David C Rupp, David Canty, Catherine Rhéaume, Birgitte Sondergaard, Celina Niño, Ron S Broide, Amy D Brideau-Andersen Allergan Aesthetics, an AbbVie Company, Irvine, CA, USACorrespondence: David C Rupp, Allergan Aesthetics, an AbbVie Company, 2525 Dupont Drive, Irvine, CA, 92612, USA, Tel +1-714-246-4059, Email david.rupp@abbvie.comObjective: The goal of this study was to compare the unit-to-unit biological activity of the vacuum-dried formulation of prabotulinumtoxinA (prabotA) and onabotulinumtoxinA (onabotA) in preclinical assays.Methods: Reconstituted 100 U vials of prabotA and onabotA were tested in 3 distinct assays: plate-capture light chain activity (PC-LCA), measuringlight chain enzymatic activity after recovery of toxin from reconstituted product using a proprietary toxin capture step; cell-based potency assay (CBPA), measuring the intoxication steps of binding, translocation, and light chain activity (synaptosomal-associated protein 25 [SNAP25] cleavage); and mouse Digit Abduction Score (DAS), evaluating muscle paresis. Each assay tested 3 separate prabotA and onabotA lots on several independent test dates.Results: Multiple orthogonal assays established that when assessed on a unit-to-unit basis, the biological activity of prabotA is lower than that of onabotA. In the PC-LCA and CBPA assays, onabotA displayed 1.51 ± 0.14-fold higher (mean ± SD) and 1.33 ± 0.07-fold higher (mean of pooled lots ± SEM) activity than prabotA, respectively. Similarly, the mouse DAS data showed that onabotA had 1.4 ± 0.1-fold higher (mean ± SEM) potency than prabotA. Results of all 3 assays demonstrated differences in potency, efficacy, and duration of action between onabotA and prabotA on a unit-to-unit basis.Conclusion: Preclinical assays established differences in the biological activity of onabotA and prabotA, supporting that the units of biological activity are not interchangeable.Keywords: pharmaceutical preparations, biological assays, enzyme assays, animal studies, motor neurons, protein binding